WADY WRODZONEModified Norwood operation for the newborn with hypoplastic left heart syndrome and Turner syndrome. A report of successful surgical treatment - Wójcik, Elżbieta; Skalski, Janusz H.; Mroczek, Tomasz; Kołcz, Jacek; Dudyńska, Mirosława; Jarosz, Jerzy; Kordon, Zbigniew; Rudziński, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Hypoplastic left heart syndrome (HLHS) is a complex cyanotic congenital heart defect with wide anatomical variability. HLHS requires multi-stage operative treatment according to the Fontan principle for single ventricle CHD. The first stage of treatment is Norwood operation performed in newborn age. Coexistence of genetic syndromes, including Turner syndrome, is an independent risk factor for the first stage of HLHS treatment by Norwood operation. The report presents the course of a successful treatment of the first stage with the modified Norwood operation of a newborn with prenatal diagnosis of Turner syndrome and CHD of type HLHS.